(untitled) (Journal of Psychiatrists’ Association of Nepal, 2020)
Introduction: Enhancing wellbeing and lessening emotional distress are especially important in developing nations like Nepal that have limited mental health resources or where there is resistance to formal treatment. This is even more so the case during times of crisis. The goal of this project was to create a cross-cultural adaptation of a psychoeducational instrument, Healthy Habits of Emotional Wellbeing. Material and Method: Using World Health Organization guidelines for translations, we created a cross cultural adaptation of Healthy Habits of Emotional Wellbeing into the Nepali language. The instrument was translated from English to Nepali, extensively reviewed and modified by a bilingual panel, back-translated, and field testing with 10 Nepali citizens. Results: The adaptation, as tested with individuals representing Nepal’s rural and urban settings, appears to be a culturally sensitive and linguistically appropriate psychoeducational tool that can be used in medical and social settings, widely disseminated, and posted online. Conclusion: Psychoeducational self-help tools such as Healthy Habits may be especially helpful during times of crisis, when mental health resources are limited, not accessible, or not accessed due to prevailing stigma. It may also be appropriate for disaster preparedness, management, and recovery use in an effective and cost efficient manner.